CUSTOMER RELATIONSHIP MARKETING PENGARUHNYA TERHADAP KEPERCAYAAN DAN LOYALITAS PERBANKAN NASIONAL - Hatane Semuel (Institute of Research and Community Outreach - Petra Christian University, 2012)
Customer relationship marketing or CRM is one of service quality form measured through commitment, communication, and complains handling. Customer trust and loyalty are expected to improve by managing those three dimensions of CRM. This research conducted to confirm CRM theoretical model in national banking industry. There are 165 respondents who participate in this research. Data are analyzed using Generalized Structured Component Analysis (GSCA). The result verifies that commitment and complaint handling of National Bank have positive effect to customer trust and customer loyalty. However, this research disconfirms communication effect to customer trust. Empirical model suggest that customer trust is intervening variable which connects CRM to customer loyalty.